Wplątanie. Derridiańska demaskacja funkcji figury „Boga” w metafizyce obecności - Bartosz Bednarczyk (Studia Philosophica Wratislaviensia)
This article is a systematic analysis of Derrida’s concept of deconstruction in terms of its critical implications regarding the function of the concept of „God” in Western theology. First, the concept of „metaphysics of presence” and its significance for the topic is explained. Then, the article considers the structure of metaphysical discourse exposed by Derrida, along with its indispensable concept of the „Absolute”. This figure turns out to have the logos function, consisting in stabilizing meanings, centralizing the discursive system, and containing the influence of chaotic différance. Finally, Derridean criticism of the figure of „God” is related to an existential problem that he discovers. This concept, thanks to its centralizing function, turns out to be a response to the terrifying experience of being entangled in the unceasing game of differentiation, a response to the instability of discourse and, finally, to human finitude.